Synanthropic triatomines (Hemiptera, Reduviidae) in the state of Pernambuco, Brazil: geographical distribution and natural Trypanosoma infection rates between 2006 and 2007 - Silva, Maria Beatriz Araújo (2012)
INTRODUCTION: The present study shows a descriptive analysis of triatomine occurrence and its natural Trypanosoma infection rates in the state of Pernambuco, Brazil, between 2006 and 2007. METHODS: Entomological data for the species, such as specimens captured in both intra and peridomiciles and natural infection index, were obtained via domiciliary capture in 147 municipalities from 11 Regional Managements of Health. The database was obtained from a sample of insects (100% infected and 20% non-infected) sent to the Central Laboratory of Pernambuco. RESULTS: A total of 18,029 triatomines were analyzed from 138 municipalities of the state. Triatoma pseudomaculata (35%), Triatoma brasiliensis (34%), and Panstrongylus lutzi (25%) were the most captured species. These species also showed a widespread geographical distribution in the state. Panstrongylus megistus, Triatoma petrocchiae, Triatoma melanocephala, Triatoma sordida, Rhodnius nasutus, Rhodnius neglectus, and Triatoma infestans showed more limited geographical distribution and lower relative abundance. The parasitological research showed that 8.8% of the triatomines were naturally infected with flagellates morphologically similar to Trypanosoma cruzi and 91.3% of them were captured inside houses in 113 municipalities. P. lutzi showed the highest rates of natural infection. CONCLUSIONS: After the control of T. infestans, synanthropic species, such as T. brasiliensis, T. pseudomaculata, and P. lutzi, maintain the risk of T. cruzi transmission to humans in the state of Pernambuco. These species are widely distributed, and infected specimens have been found inside houses. Thus, an enhanced surveillance and vector control of Chagas disease is recommended in Pernambuco.